Balong District Assessment Report, Kumba Division, Cameroons Province (Colonial Letters and the Contact of Knowledges, 1923)
This file contains colonial memoranda and assessment report on Balong District, Kumba Division, Cameroons Province
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Colonial Intelligence Report; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies